Efficiency evaluation of some novel disinfectants and anti-bacterial nanocomposite on zoonotic bacterial pathogens in commercial Mallard duck pens for efficient control - Latef, Gihan K Abdel; Mohammed, Asmaa N (Journal of Advanced Veterinary and Animal Research, 2021)
Objective: This work aimed to detect the frequency of pathogenic bacteria of zoonotic importance in ducks’ dropping, their surrounding environment, and farmworkers in contact with them. Furthermore, the susceptibility pattern of isolated bacteria to antimicrobial drugs and the efficiency of disinfectants (CID 20, Durak® plus, and hydrogen peroxide (H2O2), nano zinc oxide (ZnO NPs), and hydrogen peroxide loaded nano zinc oxide (H2O2/ZnO NPs) composites against isolated bacteria were evaluated. Materials and Methods: A total of 271 samples were collected from duck pens, including 35 fecal droppings, 200 environmental samples, and 36 from the hands of pen workers for isolation and identification of bacterial strains using standard microbiological procedures. After that, the antibiotic sensitivity testing of 40 bacterial isolates was carried out using disk diffusion assay. ZnO NPs and H2O2/ZnO NPs were characterized using Fourier-transform infrared spectrum and high-resolution transmission electron microscopy. The efficacy of disinfectants and nanocomposites was evaluated against enteropathogenic bacteria using the broth macro-dilution method. Results: The results showed that the overall prevalence of pathogenic bacteria in duck pens was 62.73. The highest isolation rate was detected in duck fecal droppings (100%), while Escherichia coli was found to be the most isolated pathogen (56.47%), followed by Pseudomonas aeruginosa (21.8%), Proteus mirabilis (15.29), and Salmonella species (6.47%). Multidrug resistance (MDR) was detected in the majority of bacterial isolates. The efficiency of CID 20 and Durak® plus disinfectants against all bacterial isolates was highly susceptible (100%) after 120 min of exposure time compared to the effectiveness of H2O2 on enteropathogenic bacteria which did not exceeded 60% at 5% concentration. Meanwhile, the sensitivity of Salmonella spp. to Durak® plus did not exceeded 80%. Conclusion: The duck fecal droppings are the primary source of bacterial isolates. MDR isolates were susceptible to both CID 20 and Durak® plus disinfectants after 120 min of exposure time at a concentration of 1:100 ml. Besides, H2O2/ZnO NPs composite proved its lethal effect against all testing strains at 0.02 mg/ml after 120 min of exposure. Strict biosecurity guidelines are required to mitigate and prevent the transmission of potentially zoonotic pathogens through the farm environment and/or duck droppings. J. Adv. Vet. Anim. Res., 8(1): 105-115, Mar 2021 http://doi.org/10.5455/javar.2021.h492